Group versus individual liability: A field experiment in the Philippines - Xavier Giné; Dean S. Karlan (Yale University, Economic Growth Center, 2007)
Group liability is often portrayed as the key innovation that led to the explosion of the microcredit movement, which grew with the Grameen Bank in the 1970s and continues on today with hundreds of institutions around the world. Group liability claims to improve repayment rates and lower transaction costs when lending to the poor by providing incentives for peers to screen, monitor and enforce each other's loans. However, some argue that group liability creates excessive pressure and discourages good clients from borrowing, jeopardizing both growth and sustainability. Therefore, it remains unclear whether group liability improves the lender's overall profitability and the poor's access to financial markets. We worked with a bank in the Philippines to conduct a field experiment to examine these issues. Working with 169 previously formed group liability centers of approximately twenty women, we converted half to individual-liability centers (treatment) and kept the other half as-is with group liability (control). The weekly group meetings still occurred; only the group liability is removed. After one year, we find no increase in default and we find higher outreach due to more new clients joining the treatment groups.
Keywords: C93; D71; D82; D91; G21; O12; O16; O17; 330; microfinance; group lending; group liability; joint liability; social capital; microenterprises; informal economies; outreach